2019
DOI: 10.1016/j.puhe.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

The health risks of informal waste workers in the Kathmandu Valley: a cross-sectional survey

Abstract: To describe the health and occupational risks of informal waste workers (IWW) in the Kathmandu valley and explore factors associated with not using personal protective equipment (PPE). Study Design A cross-sectional survey of IWWs. Method Data was collected on the health and occupational risks of adult IWWs working on waste sites in the Kathmandu Valley and in the adjacent Nuwakot District, Nepal in November 2017, through convenience sampling. Using a standardized health assessment questionnaire, face to face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 18 publications
(22 reference statements)
4
40
0
6
Order By: Relevance
“…The lowest lifetime prevalence of 3.4% reported by Black et al (2019) was observed in a comparatively large sample of waste pickers in Nepal and the highest lifetime prevalence (61.6%) was reported by Afon (2012) in a study of waste pickers working in Nigeria. The large range could be a result of differing medical waste disposal practices in each country whereby infectious medical waste is separated and disposed of separately in one country, reducing exposure to informal collectors, and frequently co-disposed in another.…”
Section: Sharps and Needlestick Injuries To Informal Waste Collectorsmentioning
confidence: 84%
See 1 more Smart Citation
“…The lowest lifetime prevalence of 3.4% reported by Black et al (2019) was observed in a comparatively large sample of waste pickers in Nepal and the highest lifetime prevalence (61.6%) was reported by Afon (2012) in a study of waste pickers working in Nigeria. The large range could be a result of differing medical waste disposal practices in each country whereby infectious medical waste is separated and disposed of separately in one country, reducing exposure to informal collectors, and frequently co-disposed in another.…”
Section: Sharps and Needlestick Injuries To Informal Waste Collectorsmentioning
confidence: 84%
“…But, also the fact that HIV transmission risk is just 0.3% compared to HCV which is 3% and HBV which is 33% (Cheng et al, 2017). (Afon, 2012;Black et al, 2019;Chokhandre et al, 2017;Cunningham et al, 2012;Parizeau, 2015;Patwary et al, 2011a).  Particular risk to medical waste handling specialists in the informal recycling sector with four sources indicating the practice (Patwary et al, 2011a;Stringer, 2011;Taghipour and Mosaferi, 2009;Unicomb et al, 2018).…”
Section: Waste Workers (Informal)mentioning
confidence: 99%
“…14 Similar findings were reported by Suri et al in their study among workers among manufacturing sector of India. 15 The workers in such chemical processing industries may have shift works leading to irregular food intake and may usually be exposed to heat stress during mechanical operations which might be the reason behind the development of diabetes mellitus as pointed out by Black et al 16 Chemical agents may cause hearing loss when acting alone or in interaction with the noise. Audiometry findings in our study revealed that 3% of the workers had mild to moderate hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Few recyclers are aware of the possible links between their activities and environmental pollution, as well as with diseases they might get [7]. For example, studies by Ohajinwa, Van Bodegom [13] and Black, Karki [15] showed that few recyclers wear PPE in their daily activities.…”
Section: Introductionmentioning
confidence: 99%